2015
DOI: 10.1088/1748-3190/10/4/046008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of running with compliant curved legs

Abstract: Running with compliant curved legs involves the progression of the center of pressure, the changes of both the leg's stiffness and effective rest length, and the shift of the location of the maximum stress point along the leg. These phenomena are product of the geometric and material properties of these legs, and the rolling motion produced during stance. We examine these aspects with several reduced-order dynamical models to relate the leg's design parameters (such as normalized foot radius, leg's effective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…This simple model effectively describes the locomotion of a great variety of different animals (including humans) that use running and hopping gaits [34], and has been successfully translated into several robotic prototypes. Straightforward replicas of compressible legs have employed pneumatic elements [35] or elastic springs [36,37], whereas more elaborate designs have used flexible structural elements [38,39], a C-shaped foot [40,41], bow-like legs [42] or springs that mimic muscle-tendon systems [43]. Similar to multi-legged animals [34], multi-legged robots could base their locomotion on the SLIP model by considering the equivalent contribution of parallel springs [44], so that the system is considered to have a single virtual leg.…”
Section: Legged Locomotion: Hopping Running and Walkingmentioning
confidence: 99%
“…This simple model effectively describes the locomotion of a great variety of different animals (including humans) that use running and hopping gaits [34], and has been successfully translated into several robotic prototypes. Straightforward replicas of compressible legs have employed pneumatic elements [35] or elastic springs [36,37], whereas more elaborate designs have used flexible structural elements [38,39], a C-shaped foot [40,41], bow-like legs [42] or springs that mimic muscle-tendon systems [43]. Similar to multi-legged animals [34], multi-legged robots could base their locomotion on the SLIP model by considering the equivalent contribution of parallel springs [44], so that the system is considered to have a single virtual leg.…”
Section: Legged Locomotion: Hopping Running and Walkingmentioning
confidence: 99%
“…21,22 Some work has investigated how the shape of the leg can be used to achieve variable stiffness and relative leg length changes during the stance phase. 23,24 Similarly, Owaki et al…”
Section: Introductionmentioning
confidence: 93%
“…21,22 Some work has investigated how the shape of the leg can be used to achieve variable stiffness and relative leg length changes during the stance phase. 23,24 Similarly, Owaki et al investigated different nonlinear stiffness functions and identified the ones that are beneficial, 25 although this was done using a compass gate, rather than the SLIP model. Andrews et al explored changing the length of the spring, rather than its stiffness in their work.…”
Section: Introductionmentioning
confidence: 99%
“…The spring constant is chosen according to the optimal variable table from our previous research [13]. The damping coefficient is chosen from the existing spring damping ratio in [15] with its several multiples. The damper is designed by using the principle of a coaxial rotating cylinder viscometer [16,17].…”
Section: Robot Designmentioning
confidence: 99%